Characterisation of porous hydroxyapatite beads prepared from fish scale for potential bone filler applications - Zainol, Ismail; Zainurin, Mira Azah Najihah; Abu Bakar, Nurul Hidayah; Jaafar, Che Nor Aiza; Mudhafar, Mustafa (Universiti Putra Malaysia, 2022)
The aim of this study is to prepare the different sizes of porous HA beads from fish scales hydroxyapatite (FsHA) using sieve technique. Different composition of porous agents (0 to 20 wt%) were used to prepare different porosity of FsHA beads. The FsHA beads was sintered at 1200 °C in open air for four hours at heating rate of 3 °C min-1. The FsHA beads were characterized using Fourier transform infrared spectroscopy (FTIR), x-ray diffraction (XRD) and scanning electron microscope (SEM). The physical properties of FsHA beads such as density and porosity were determined using pycnometer method. The linear shrinkage was carried out by calculating the shrinkage percentage as sintered. The sintered FsHA beads was confirmed to be crystalline hydroxyapatite since the FTIR spectra shows the sharps absorption peaks at 550 and 600 cm-1 and 1100-1200 cm-1 which are corresponding to the phosphate groups. The XRD analysis has confirmed the pattern of hydroxyapatite with sharp peaks was observed at (211), (112) and (300), characteristics to the high crystallinity of hydroxyapatite. The results showed that as the amount of porous agent (tapioca starch) increase from 0 to 20 wt% , the porosity was increased from 33 to 61 %, meanwhile the density was decreased from 3.0 to 1.64 g cm-3. SEM analysis shows the mesoporous structure of FsHA beads at different composition of porous agent. The percent of shrinkage of different composition of porous agent are slightly similar to each other which about 10 to 12 %. The high porosity with low density of hydroxyapatite bead has potential to be used as bone filler.